Sugarcane Trench Planting and SSNM formula changing farmer’s life - Katiyar, A K; Singh, B B; Dixit, Rakesh (Indian Farming, 2016)
Trench method for sugarcane planting requires two budded sets and 17.5 q/ ha more seed along with Rupees 4000-5000 for nutrients, as SSNM formula and 10 more days were used during planting. This increased yield by 50% due to trench method of planting and 50% by site specific nutrient management.